Assessment of toxic metal contamination with ecological risk of surface water and sediment of Korotoa River in Bangladesh - Proshad, Ram; Saiful Islam, Md.; Kormoker, Tapos; Emam Mehedi Masud, Md.; Mohammad Ali, Mir. (International Journal of Advanced Geosciences, 2018)
Toxic metal contamination is a major problem globally, especially in developing countries. In this study, the levels of toxic metals such as Cr, Ni, Cu, As, Cd and Pb in surface water and sediment of Korotoa River of Bogra City, Bangladesh were investigated. The average concentration of Cr, Ni, Cu, As, Cd and Pb in studied sediment were 1.01, 0.89, 1.98, 6.02, 0.0054 and 0.469 mg/kg, respectively. In the water sample, the mean concentration of Cr, Ni, Cu, As, Cd and Pb were 1.13, 1.33, 3.02, 2.62, 0.75 and 0.81 mg/kg, respectively. A huge amount of municipal wastes, industrial effluents and agricultural runoff from the periphery of Bogra City notably are dumped to this river. Most of the effluents channeled into these rivers are not treated. Considering the sampling sites, the decreasing order of total metal concentration in water samples were Cu > As > Ni > Cr > Pb > Cd and in sediment were As > Cu > Cr> Ni > Pb > Cd. Total average concentrations of Cr, Ni, Cu, As, Cd and Pb in the water samples were higher than WHO guidelines for drinking water quality. This contamination level implied that the condition is much frightening and probably severely affecting the aquatic ecology of the river.Â Â
Keywords: Toxic metal; surface water; sediment; Korotoa River; ecological risk; Bangladesh